Micromechanical aspects of fibre/crack interactions in an aramid/epoxy composite - Bennett, J. A.; Young, R. J.
Raman spectroscopy has been used to study the effect of matrix cracking on the deformation micromechanics of untreated and adhesion-activated Twaron aramid fibres embedded in an epoxy matrix,' by monitoring the shift in the peak position of strain-sensitive Raman bands. The point-to-point distribution of strain was measured in those aramid fibres in the vicinity of the crack tip and in those bridging the faces of the crack, thus enabling the modes of interfacial failure to be monitored. Initially, strain profiles were mapped for an array of fibres behind the crack tip in an unloaded specimen, showing that dynamic cracking caused debonding of the jibre/matrix interface and that jibre fracture did not occur. The length of the debond was shown to increase with distance of the ftbre behind the crack tip. The extent of debonding was also found to be dependent on the fibre surface treatment. The specimen was subsequently reloaded incrementally and the build-up of stress in fibres ahead of the crack tip was monitored. It was possible to detect, in some cases, interfacial debonding at or ahead of the crack tip. The behaviour of the jibres bridging the faces of the crack was observed during reloading and it was shown that further propagation of the debond during static loading was controlled by the fibre surface treatment.
Keywords: ARAMID FIBRES; COMPOSITES; RAMAN SPECTROSCOPY; CRACK BRIDGING